Fresno County Counsel Office Holiday Party - Watkins, Howard::::::::: (1985)
Floyd Viau, Pamela Stone, Max Robinson, Peggy Smith opening her present, John Duffy, Vickie Stoutingberg 12-inch BW Television on filing cabinet; 12-line double unit desktop telephone